2020
DOI: 10.1038/s41598-020-69058-z
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence and distribution of vancomycin resistant, vancomycin intermediate and heterogeneously vancomycin intermediate Staphylococcus aureus clinical isolates: a systematic review and meta-analysis

Abstract: Vancomycin-resistant Staphylococcus aureus (VRSA), Vancomycin-intermediate S. aureus (VISA) and heterogeneous VISA (hVISA) are subject to vancomycin treatment failure. The aim of the present study was to determine their precise prevalence and investigate prevalence variability depending on different years and locations. Several international databases including Medline (PubMed), Embase and Web of Sciences were searched (data from 1997 to 2019) to identify studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
126
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(172 citation statements)
references
References 198 publications
7
126
4
Order By: Relevance
“…More so, vancomycin resistance may also be caused by decreased permeability by thickening the cell wall, thus inhibiting/decreasing vancomycin availability to intracellular target molecules [ 58 ]. High percentage resistance to teicoplanin was also observed in the study; however, this was not peculiar, as cross-resistance between glycopeptides has been reported [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…More so, vancomycin resistance may also be caused by decreased permeability by thickening the cell wall, thus inhibiting/decreasing vancomycin availability to intracellular target molecules [ 58 ]. High percentage resistance to teicoplanin was also observed in the study; however, this was not peculiar, as cross-resistance between glycopeptides has been reported [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 54%
“…This finding was similar to that of Sieber et al in a Danish study on LA-MRSA in pigs and humans [ 51 ]. However, other studies have reported a comparatively higher prevalence of tet M than tet K [ 52 , 53 ]. It has been established that most MRSA harbour both tet K and tet M, which confer resistance to all tetracycline antibiotics [ 54 ].…”
Section: Discussionmentioning
confidence: 96%
“…Deep wound infection (p = 0.043), previous wound infection (p = 0.006) and hospital stay > 72 h (p = 0.001) also demonstrated an association with MRSA infection. Unlike our study a studies by Shariati, (2020) found an association between several variables (hemodialysis dependence, long-term use of vancomycin, hospitalization in ICU and use of indwelling devices ) [27]. Apparent absence of association between variables and VRSA in the present study might be due to small sample size.…”
Section: Discussioncontrasting
confidence: 96%
“…3) (VISA &VRSA). With this cut of value, our nding becomes comparable with several countries [8,24,25].…”
Section: Discussionsupporting
confidence: 65%
“…Altogether, occurrence of isolates with reduced susceptibility to vancomycin has increased over the last years probably also due to more frequent use of vancomycin in patients with MRSA infections ( 51 ). However, prevalence is still low with under 5% and daptomycin remains an effective treatment option in these isolates ( 52 , 53 ).…”
Section: Current Diagnostic and Treatment Standardsmentioning
confidence: 99%